2021
DOI: 10.1371/journal.pone.0245825
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of preterm birth among women delivered in public hospitals of Western Ethiopia, 2020: Unmatched case-control study

Abstract: Background Worldwide, preterm birth accounts for 1 million deaths of infants each year and 60% of these deaths occur in developing countries. In addition to the significant health consequences on the infant, preterm birth can lead to economic costs. There was a lack of study in western Ethiopia, and most of those studies conducted in other parts of a country were based on card review with a cross-sectional study design. The risk factors of preterm birth may vary from region to region within the same country du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
5
25
1
Order By: Relevance
“…Women with preterm deliveries were nine times at higher risk of adverse obstetric outcomes. This finding was supported by a study done in Western Ethiopia, where mothers who developed anemia during pregnancy, PROM, and PIH were more likely to experience preterm birth [ 25 ]. Anemia may induce maternal and fetal stress and increase the risk of maternal infection stimulating the production of corticotropin-releasing hormone (CRH).…”
Section: Discussionsupporting
confidence: 60%
“…Women with preterm deliveries were nine times at higher risk of adverse obstetric outcomes. This finding was supported by a study done in Western Ethiopia, where mothers who developed anemia during pregnancy, PROM, and PIH were more likely to experience preterm birth [ 25 ]. Anemia may induce maternal and fetal stress and increase the risk of maternal infection stimulating the production of corticotropin-releasing hormone (CRH).…”
Section: Discussionsupporting
confidence: 60%
“…More than three-quarters (81.1%) of all PBs occur in Africa and South Asia (2). PB is a major Elmugabil et al 10.3389/fnut.2022.933557 cause of perinatal death and a significant cause of longterm consequences among the survivors (3). PB is the main direct cause of neonatal death and is associated with 50-75% of all neonatal mortality and half of all neonatal morbidity worldwide (4).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for PB should be correctly identified and properly managed to reduce the incidence of PB. Maternal nutrition may impact both haemoglobin synthesis and foetal growth, development, survival, and PB (10,11). Previous studies on the association between the haemoglobin level and PB showed inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…It is consistent with study conducted in British and South Ethiopia where any additional dietary supplementation is associated with preterm birth. 17 , 31 The reason behind this fact is during pregnancy women need additional meals for themselves, their fetus, and pregnancy outcomes. 32 If pregnant women do not get additional food, then they can face malnutrition (thinness).…”
Section: Discussionmentioning
confidence: 99%
“…6 Some of the risk factors of preterm birth are undernutrition, obesity, anemia, unable to obtain dietary supplements, not consuming vegetables, and low maternal weight, low income. 5,[10][11][12][13][14][15][16][17] Although the fact that eating patterns throughout pregnancy have a critical role in the health of both the mother and the baby and pregnant women have to eat variety of food in addition to taking additional food; nutritional-related predictors of preterm delivery have yet to be examined. [18][19][20] Despite the high prevalence of preterm birth in Ethiopia, which causes a variety of morbidities and mortality in mothers and babies, as well as economic losses, no research has been done on nutritional-related predictors of preterm delivery.…”
Section: Introductionmentioning
confidence: 99%